Total Hip Arthroplasty in Patients Under 50 Years of Age: A Demo-graphic and Treatment Outcome Study at Five Years Follow-Up - Banskota, Bibek; Rajbhandari, Ansul; Aryal, Rajendra; Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2023)
Introduction: The indications for a total hip arthroplasty have expanded to younger, higher-demand patients with the advances and availability of durable biomaterials and improved accuracy and surgical techniques of prosthesis implantation. We present our data on the mid-term (five years) follow-up of a cohort of younger patients who underwent THA at our institution.Methodology: A retrospective study with prospective measurement of functional and patient satisfaction outcomes was conducted for patients under 50 years of age who had undergone a primary THA for any cause from 2010 to 2020. Study variables included demographic profile, etiology, prosthesis details, pre-and post-Harris Hip Scores (HHS), and the short-form SF-12 questionnaire.Results: Of 206 THAs performed during the study period, 62 (30.09%) THAs met the inclusion criteria. There were 60 patients with 62 hips, including 38 (63.33%) males and 22 (36.67%) females. The mean age was 39.2±7.92 years. The mean pre-operative HHS was 40.10±5.96. The mean follow-up period was 5.14±2.57 years. At the final evaluation, the mean HHS was 90.42±6.35, and SF-12 scores for physical (PS) and mental (MS) domains were 46.98±5.76 and 54.22±4.35, respectively. The HHS was excellent in 45 (72.58%) hips, good in 13 (20.96%) hips, fair in 2 (3.23%) hips, and poor in 2 (3.23%) hips.Conclusion: Good to excellent functional results were seen in 94% of patients at five years follow-up. Uncemented prostheses and ceramic-on-polyethylene bearing surfaces were preferred.